1979
DOI: 10.3109/01485017908985066
|View full text |Cite
|
Sign up to set email alerts
|

The leprous testis

Abstract: A clinical investigative study of 148 male leprous patients demonstrated the presence of testicular lesions in 35 cases. Semen analysis revealed marked oligo-athenozoospermia in 10 cases and azoospermia in 25 cases. Testicular biopsies from leprous testes showed different histologic patterns ranging from spermatogenic arrest to complete hyalinization of both seminiferous tubules and interstitial tissue. Histochemical staining for neurovascular supply revealed degenerative nerve change in addition to altered pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Lepromatous leprosy is associated with an increased risk of semen abnormalities and azoospermia with testicular biopsies showing features of spermatogenic arrest as well as complete hyalinization of both seminiferous tubules and interstitial tissue (El-Beheiry et al ., 1979; Saporta and Yuksel, 1994). Data from Tanzania have suggested lower fertility in men and women suffering from malaria although the pathogenesis remains to be explained (Larsen, 1996).…”
Section: Aetiology and Risk Factors For Infertility In Developing Coumentioning
confidence: 99%
“…Lepromatous leprosy is associated with an increased risk of semen abnormalities and azoospermia with testicular biopsies showing features of spermatogenic arrest as well as complete hyalinization of both seminiferous tubules and interstitial tissue (El-Beheiry et al ., 1979; Saporta and Yuksel, 1994). Data from Tanzania have suggested lower fertility in men and women suffering from malaria although the pathogenesis remains to be explained (Larsen, 1996).…”
Section: Aetiology and Risk Factors For Infertility In Developing Coumentioning
confidence: 99%
“…Infertility has been reported in 24% to 28% male patients with leprosy, with oligoazoospermia in 61% to 69% of lepromatous patients. 4 El-Shiemy et al 8 opined that azoospermia was a result of testicular involvement, rather than epididymal obstruction. Abd-Elkawi et al 3 proposed that the degree of testicular involvement, duration of disease, early treatment, and frequency of orchitis in type 2 reactions influenced testicular atrophy, whereas El-Beheiry et al 4 found no relation between duration of disease and testicular involvement.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Testicular involvement may or may not correlate with disease progression. 2,4 The testes are composed of Leydig cells and seminiferous tubules containing Sertoli cells and germ cells. Leydig cells produce testosterone under regulation by luteinizing hormone (LH), and Sertoli cells are regulated by follicle stimulating hormone (FSH) and androgens.…”
Section: Introductionmentioning
confidence: 99%
“…Epididymo-orchitis, scrotalgia and orchitis are common urological ailments. Testicular involvement by leprosy is quite common, incidence ranging from 23.6% to 68.3% [2,3]. India accounts for half of the leprosy burden of the world.…”
Section: Discussionmentioning
confidence: 99%